2022
DOI: 10.3991/ijet.v17i10.25819
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Student Internet Access and Teachers’ Self-Efficacy in Teaching Online Classes

Abstract: The most critical requirement of an online class is the availability of the internet for a teacher and students alike. The objective of this study was to find out how student internet access correlates to teachers’ self-efficacy in teaching an online class. This quantitative study used categorical data obtained using two questionnaires, one of which was student internet access consisting of three constructs, and the other is teachers’ self-efficacy in teaching an online class. The questionnaires were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…This highlights teachers' need to upskill and adapt to new pedagogical concepts and modes of teaching delivery [20]. Increasing feelings of confidence and motivation amongst teachers will likely have a positive impact on students' online learning experience and students will be more likely to embrace this mode of learning [19,23]. A review conducted by Pettersson highlighted that 'students need competent and confident teachers to make use of rich digital learning environments' [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights teachers' need to upskill and adapt to new pedagogical concepts and modes of teaching delivery [20]. Increasing feelings of confidence and motivation amongst teachers will likely have a positive impact on students' online learning experience and students will be more likely to embrace this mode of learning [19,23]. A review conducted by Pettersson highlighted that 'students need competent and confident teachers to make use of rich digital learning environments' [24].…”
Section: Discussionmentioning
confidence: 99%
“…A review conducted by Pettersson highlighted that 'students need competent and confident teachers to make use of rich digital learning environments' [24]. Studies have shown that training and perception of proficiency helps educators to develop confidence to engage learners and this impacts on performance, satisfaction and outcome [23]. However, in comparison to institutions based in High-Income countries, higher education institutions such as OAU are likely to have less resources and funds available for training and development of their teaching staff [5].…”
Section: Discussionmentioning
confidence: 99%
“…These results for students may also be positive for teachers. Often, teacher self-efficacy in online environments correlates with student participation, and in the online environment that participation equates with internet access (Mustafa et al, 2022).…”
Section: Online Learningmentioning
confidence: 99%
“…Internet está cambiando las funciones de los participantes del proceso educativo (Ibragimov et al, 2023;Mustafa et al, 2022); por ejemplo, las aplicaciones web educativas fomentan la autonomía de los estudiantes y permiten el aprendizaje personalizado (Salas-Rueda & Alvarado-Zamorano, 2022).…”
Section: Introductionunclassified